“I’m Not a Child Molester, But a Victim Myself”: Examining Rationalizations Among Male Sex Offenders Who Report Histories of Childhood Sexual Abuse - Steely Smith, Mollee (International journal of offender therapy and comparative criminology, 2023)
Persons convicted of sexual offenses (PCSOs) hold distorted attitudes and beliefs, or rationalizations that minimize the severity of their offending. Despite this, knowledge of rationalizations held by PCSOs remains limited, especially for offenders who report being sexually abused as children. The purpose of the study was to qualitatively assess post-conviction rationalizations of PCSOs who reported childhood sexual abuse (n = 40) and those who reported no sexual abuse (n = 40) focusing on account variations—a framework proposed by Scott & Lyman. Offenders were interviewed and assessed for risk and community notification purposes in 2014 in a southern state. The manner in which PCSOs use rationalizations to avert responsibility for their offenses provides insight into their motivations for offending, and therefore, can inform treatment initiatives for PCSOs with and without histories of sexual victimization. Results can help inform differentiated treatment for those with histories of sexual abuse and those without.